2021
DOI: 10.1186/s12958-021-00719-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polycystic ovary syndrome among Flo app users around the world

Abstract: Background Polycystic ovary syndrome (PCOS) is a complex and multi-faceted endocrine disorder that affects 5–20% of women. Literature is limited regarding potentially differing PCOS phenotypes among women around the world. Objective To use Flo app technology to understand the multifaceted characteristics of PCOS across several countries and identify contributing risk factors to the development of this condition. Study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…For women in our study, irregular periods were their top concern related to PCOS (63%). This is similar to a previous study conducted by Jain et al, where they reported irregular periods (66%) as the third most common symptom of PCOS in Indian women [ 43 ]. Therefore, educating women about menstruation and its irregularities is an important aspect of diagnosis and treatment planning.…”
Section: Discussionsupporting
confidence: 92%
“…For women in our study, irregular periods were their top concern related to PCOS (63%). This is similar to a previous study conducted by Jain et al, where they reported irregular periods (66%) as the third most common symptom of PCOS in Indian women [ 43 ]. Therefore, educating women about menstruation and its irregularities is an important aspect of diagnosis and treatment planning.…”
Section: Discussionsupporting
confidence: 92%
“…Such functionality includes menstrual cycle and pregnancy tracking or tracking of cycle-related symptoms, e.g. hormone triggered migraines or mood swings [50][51][52][53]. Previous studies have shown that health mobile apps also facilitate good habits formation and health promotion by providing a number of functions to map behaviour patterns across time, including, but not limited to, sleep, diet, physical activity, mental health practices etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to tracking functionality, Flo provides its users with evidence-based and expert-reviewed educational content available through the in-app library. To check for symptoms against an array of conditions, Flo also has interactive questions available via so-called 'health assistants' or 'chatbots' [52]. Finally, Flo has a secure place called 'Secret Chats' where women can discuss intimate topics, ask questions anonymously, and get support from millions of women worldwide, thus reducing perceived taboos and stigma surrounding topics such as menstrual health and sexual life [58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory imbalances between reproduction and metabolism caused by disorders such as PCOS (in which symptoms are due to elevated androgen levels) often result in ovarian dysfunction, and increase the risk of cardiovascular and metabolic disorders in women ( Dokras, 2013 , Studen and Pfeifer, 2018 , Torchen, 2017 ). PCOS is a complex and multi-faceted endocrine disorder in women of reproductive age, affecting approximately 2–20% ( Jain et al, 2021 , Pal, 2014 ), depending on the clinical inclusion criteria. PCOS impacts various aspects of a woman's life, such as aesthetics, reproduction, metabolism, psychological well-being and sexuality ( Aversa et al, 2020 ).…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%